TURNER SYNDROME WITH ARNOLD CHIARI TYPE I MALFORMATION – A CASE REPORT - MI, Muntarui; M, Noordin; NSM, Nor (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Turner Syndrome (TS) is a genetic disease caused by absence of one X chromosome, and is uncommonly linked with congenital CNS abnormalities. Arnold-Chiari Malformation is rarely associated with TS. Furthermore, there are limited reports available on the outcome of growth hormone (GH) therapy in this group of patients. CASE We described a 17-year-old female who was referred to us 3 years ago due to suspicion of TS in view of dysmorphism, short stature and primary amenorrhea. Her karyotyping confirmed 45,X. Her height at presentation was 132 cm (- 4.98 SDS), weight 45.55 kg (-1.28 SDS), BMI of 26 kg/m2 (+1.72 SDS), with MPH 153 cm. She was prepubertal with Tanner staging of A1, B1, PH1. In consistent with primary gonadal failure, her LH and FSH were elevated at 18.1 IU/L and 95 IU/L respectively with low Oestradiol <18.3 pmol/L. Her renal ultrasound was normal. www.memsmac.org She has no other endocrinopathies. Her other comorbidities include coarctation of aorta, bicuspid aortic valve with severe aortic stenosis, post-balloon valvulotomy and coarctation repair. In view of her short stature, she was planned for GH therapy. Assessments pre-GH therapy revealed an incidental finding of central apnoea from polysomnography with an Apnoea-Hypopnea Index (AHI) of 22.5/H. This has led to MRI brain that revealed cerebellar tonsil descended 7 mm below the foramen magnum, consistent with Arnold-Chiari Type I malformation. CONCLUSION This case highlights the challenge of initiating GH therapy for a patient with Turner Syndrome and Arnold Chiari Type I malformation. Proper counselling with the patient and family is crucial to balance the harm and benefit of GH therapy. The decision to start GH therapy requires multidisciplinary management with close follow-up to monitor any complications and to avoid adverse events.